-2
$\begingroup$

Proof of $(A+B) \times (A-B) = -2(A \times B)$, where 'A' and 'B' are vectors

$\endgroup$
1
  • $\begingroup$ What about said proof? $\endgroup$
    – MPW
    Apr 23, 2016 at 4:50

1 Answer 1

1
$\begingroup$

Using the distributive law, $$(A+B)\times(A-B)=A\times A-A\times B+B\times A-B\times B$$ $$A\times A=B\times B=0$$ $$(A+B)\times(A-B)=0-A\times B+B\times A-0$$ $$B\times A=-A\times B$$ $$(A+B)\times(A-B)=-A\times B-A\times B=-2(A\times B)$$

$\endgroup$

Not the answer you're looking for? Browse other questions tagged .